Isolate two Crustaceans which infect Cyprinus carpio L. from Bab Al-Muatham fish markets, Baghdad City: Nahla Talib Mansoor, Sadiq M. Jawad Al-Shaikh - Al-Shaikh, Sadiq M. Jawad (The Iraqi Journal of Veterinary Medicine, 2011)
During the period from November 2007 till October 2008, a total of 255 specimens of the cyprinid fish, from freshwater fish Cyprinus carpio Linnaeus, 1758, were collected from fish markets east of Baghdad city. Microscopic examination of these fishes revealed that they were infected with two species of the crustaceans ]Argulus foliaceus (0.8%) and Ergasilus sieboldi (20%)[.The present study included the following: The clinical signs which were caused by the crustaceans, which included redness and an opacity of the skin, increase of mucus secretion and rapid movements of the operculum. The percentage incidence of the infection with these parasites were also found to be related to different length groups of the host, the larger fishes were more infected (95.2%) while the smaller fishes were less infected (0.8%).